A review of consumer preferences of and interactions with electric vehicle charging infrastructure. (July 2018) - Hardman, Scott; Jenn, Alan; Tal, Gil; Axsen, Jonn; Beard, George; Daina, Nicolo; Figenbaum, Erik; Jakobsson, Niklas; Jochem, Patrick; Kinnear, Neale; Plötz, Patrick; Pontes, Jose; et al.
Highlights: Studies on consumers and plug-in electric vehicle (PEV) infrastructure are reviewed. These studies use various data from consumers, vehicles, and charging equipment. Conclusions and policy recommendations are made where possible. More research is needed to inform the development of PEV charging infrastructure. Research is needed on 200 mile range BEVs and how much infrastructure is needed. Abstract: This paper presents a literature review of studies that investigate infrastructure needs to support the market introduction of plug-in electric vehicles (PEVs). It focuses on literature relating to consumer preferences for charging infrastructure, and how consumers interact with and use this infrastructure. This includes studies that use questionnaire surveys, interviews, modelling, GPS data from vehicles, and data from electric vehicle charging equipment. These studies indicate that the most important location for PEV charging is at home, followed by work, and then public locations. Studies have found that more effort is needed to ensure consumers have easy access to PEV charging and that charging at home, work, or public locations should not be free of cost. Research indicates that PEV charging will not impact electricity grids on the short term, however charging may need to be managed when the vehicles are deployed in greater numbers. In some areas of study the literature is not sufficiently mature to draw any conclusions from. More research is especially needed to determine how much infrastructure is needed to support the roll out of PEVs. This paper ends with policy implications and suggests avenues of future research.